Catfish and Tilapia Farming Business Based on Probio FM Technology at CV. DAM Petaling Village, Bangka - Kurniawan Kurniawan; Feni Marlinda; Lanang Satria Wiralaga; Sudirman Adibrata; Yeyen Mardyani; Riza Safira (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2022)
Universitas Bangka Belitung students carry out Merdeka Belajar Kampus Merdeka (MBKM) activities in the Kedaireka Matching Fund Program in 2022 with the title of the activity, namely the Cultivation of Catfish and Tilapia Based on Probio FM Technology at CV DAM Petaling Village, Bangka Regency. The purpose of this entrepreneurial activity is to accelerate the production of catfish and tilapia cultivation using Probio FM, popularize feeding with the addition of Probio FM and form an aquaculture business group based on Probio FM technology. Probio FM is a liquid probiotic containing lactic acid bacteria that functions to improve water quality, reduce ammonia odor and fly population, reduce fishy odor in fish meat, can reduce mortality in fish and increase feed use efficiency. The methods used in this activity include surveying the location of activities, preparing land for KJA / KJT, stocking catfish and tilapia seeds, feeding fish with the addition of Probio FM, sorting, harvesting, marketing and forming business groups. The results in this activity have been harvested tilapia and catfish with a cultivation time of 2 months and 2 weeks for catfish with an average weight of 140gram. The total harvest of catfish was 330 kg and tilapia was 270 kg. A business group has been formed under the name Gerai FF Kedaireka. Probio FM is very influential on the enlargement of catfish and tilapia. It is expected that more and more farmers will use Probio FM technology.